Scientific Collaboration and Research Productivity: Evidence from One College in Makerere University - Muteesasira, Christopher; Bakkabulindi, Fredrick Edward K.; Onen, David (East African Journal of Education Studies, 2024)
In academia, the many benefits of publishing make continuous publication a cardinal duty of faculty members. Some members work as lone writers and others work collaboratively to come up with scholarly works. Benefits of collaboration come in form of filling gaps between the haves and the have not by academic staff. In this study, the aim was to establish whether research collaboration among academic staff was related to research productivity. More specifically, we examined whether collaboration in publication of edited books, chapters in edited books, journal articles, and conference papers by members of academic staff was related to their research productivity. Using collaboration and publication data on 41 academic staff members in the College of Education and External Studies, Makerere University, we analysed the relationship between the two. Results of the Karl Pearson’s linear correlation coefficient indicated that the academic staff who collaborated were more research productive. This was true for all the four forms, individually namely; edited books, chapters in edited books, journal articles, and conference papers and in terms of aggregated four forms. This study underscores the importance of cultivating collaborative environments in academia to bolster scholarly output, which is not only to the benefit of academic staff but also to university administrators and policymakers when endorsing collaborative research initiatives and interdisciplinary cooperation. Thus, it contributes to the theoretical understanding of the subject by furnishing empirical evidence on the relationship between scientific collaboration and RP by members of academic staff